In vitro digestibility and fermentation ruminant of buffalo ration based on Neptunia plena L. Benth and Leersia hexandra Swartz as local resources - Mayulu, Hamdi; Suyadi, Suyadi; Christiyanto, M.; Sunarso, Sunarso; Daru, T. P.; Haris, Muh. I. (Faculty of Animal Science, Universitas Brawijaya, 2020)
Utilization of local resource (Neptunia plena L. Benth and Leersia hexandra Swartz) as feed ration for buffalo fattening could make cost efficiency, fulfil primary life needs and production. The objectives of study is to determine the Dry Matter Digestibility (DMD), Organic Matter Digestibility (OMD), NH3 ruminant fermentation and Volatile Fatty Acid (VFA). The conduct of the study was in Laboratory of Animal Husbandry Nutrient Science, Faculty of Animal Science and Agriculture, Diponegoro University, Semarang by using in vitro method with a Complete Randomized Design (CDR) of five treatments and five replicates: (1)Â T1 =100% Leersia hexandra Swartz; (2) T2 = 100 % Neptunia plena L.Benth; (3) T3 = Ration (15% Neptunia plena L.Benth + 15% Leersia hexandra Swartz + 70% other feedstuffs); (4) T4 = Ration (20% Neptunia plena L.Benth + 20% Leersia hexandra Swartz + 60% other feedstuffs); and (5) T5 = Ration (25% Neptunia plena L.Benth + 25% Leersia hexandra Swartz + 50% other feedstuffs). Data analysis used analysis of variance with a significance level of 95% and then followed by Duncan Multiple Range Test (DMRT). The results showed that T3 and T4 treatments produced the highest DMD at (P <0.05), i.e. 43.65% and 43.26%, respectively. T2 treatment (47.66%) significantly produced the highest OMD (P <0.05) compared to T4 (46.81%) and T1 (45.36%). T5 treatment (5.28 mM) significantly produced in the highest NH3 (P <0.05) compared to T2 (4.88 mM); T3 (4.73 mM); and T1 (4.43 mM). T5 treatment (145.4 mM) significantly produced the highest VFA (P <0.05) compared to T4 (140.0 mM); T3 (135.4 mM); T2 (134.8 mM); and T1 (123.6 mM). In vitro digestibility and fermentation ruminant of buffalo ration based on Neptunia plena, L. Benth, and Leersia hexandra Swartz as local resources can buffalo improved ruminant fermentation so that it is capable of increasing the buffalo productivity.